Cutaneous angiosarcoma in a patient with xeroderma pigmentosum - Arora Raman; Sharma Alok; Gupta Ruchika; Vijayaraghavan M (Wolters Kluwer Medknow Publications, 2008)
Xeroderma pigmentosum (XP) is a rare, autosomal recessive disorder characterized by photosensitivity, cutaneous pigmentary changes, premature skin ageing and development of various cutaneous and internal malignancies at an early age as a result of a defect in nucleotide excision repair following ultraviolet light exposure. Cutaneous angiosarcomas are aggressive neoplasms that are rarely associated with XP. In this communication, we report the case of a 40-year-old male patient with XP who developed an angiosarcoma of the face and discuss the implications of this association in view of recent developments in this field.